A hybrid model for new product development - a case study in the Brazilian telecommunications segment - Sales, Odivany P. (2013)
This paper presents a hybrid model for the integrated development of products based on the decision models Funnel and Stage Gate. This hybrid model was designed in its complete and simplified versions with the main purpose of technological support in the process of developing new products based on the maturity development level of the company. The simplified model was applied in the development of a new product in a Brazilian telecommunications company through a case study, its results were described and analyzed and recommendations for the continuity of the research were presented.